2018
DOI: 10.1159/000492789
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia, Ego-Dystonicity, and Obsessive-Compulsive Symptoms: A Path Modeling Analysis

Abstract: Aims: This cross-sectional study aimed to test the path relations between alexithymia, ego-dystonicity, anxiety, depression and obsessive-compulsive (OC) symptoms in obsessive-compulsive disorder (OCD) and healthy individuals. Methods: Fifty-eight patients with OCD (mean age 35.5 years) and 54 healthy participants (mean age 33.5 years) completed an assessment via a structured clinical interview. All of them completed the Toronto Alexithymia Scale (TAS-20), the Vancouver Obsessive-Compulsive Inventory (VOCI), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
(68 reference statements)
1
0
0
Order By: Relevance
“…Obsessive thoughts are meaningless, but cause feelings of distress, anxiety, and compulsions that play a significant role in normalizing anxiety. This outcome is in line with some of the findings of Newton and Contrada [38], who showed that anxiety is listed as one of the consequences of obsessive thoughts and characterizes high alexithymia, Alexithymia in healthy persons related to the OC symptoms only through ego-dystonicity -Self-Consistency and Congruence - [39], that Alexithymia makes the individual loses congruence with himself that cause moving toward OC.…”
Section: Discussionsupporting
confidence: 90%
“…Obsessive thoughts are meaningless, but cause feelings of distress, anxiety, and compulsions that play a significant role in normalizing anxiety. This outcome is in line with some of the findings of Newton and Contrada [38], who showed that anxiety is listed as one of the consequences of obsessive thoughts and characterizes high alexithymia, Alexithymia in healthy persons related to the OC symptoms only through ego-dystonicity -Self-Consistency and Congruence - [39], that Alexithymia makes the individual loses congruence with himself that cause moving toward OC.…”
Section: Discussionsupporting
confidence: 90%